Where Patriarchy, Gender, and Verdicts Collide: Servant Theft Against their Masters in England during the Late Seventeenth and Early Eighteenth Centuries - Letawsky, Sarah (MacEwan University Student eJournal, 2016)
Servant theft against their masters during the late seventeenth and early eighteenth centuries was common and influenced by societal expectations and regulations. Strict guidelines dictated prescriptive notions of servant behaviour, which could be difficult for servants to maintain. With limited freedom under a system of service influenced by patriarchy and religion, servants chose to commit theft offences to provide a solution to their circumstances. Male and female servants usually stole items that corresponded to their occupational roles. By examining fifteen court cases tried at The Old Bailey, one can see that male and female servants demonstrated similar levels of criminality, but female servants often received harsher punishment for their thefts than male servants due to the patriarchal framework of early modern English sociaty.